The Second Wave of Independence : Shopping for Solutions - Gaarder, Marie M.; Bartsch, Ulrich (World Bank Group, Washington, DC, 2014)
In the 21st century, many developing countries will become emerging markets and will no longer be in need of the carrot-and-stick approach to development assistance most prevalent today: development financing made available conditional on certain policies and interventions. This paper suggests that interactions between development agencies and recipient governments are mostly about inputs deemed (but not known) to contribute to improvements in living standards in recipient countries, rather than outcomes. The paper argues that the development marketplace is beset by market imperfections because of externalities, principal-agent problems, and decision making under uncertainty, which not only make it difficult to achieve the right outcomes, but also take away incentives to learn about outcomes. A fundamental rethink of responsibilities and accountabilities in the development business would make sure that development outcomes are traded in the development marketplace. It would put recipient countries in charge of contracting development agencies to provide these outcomes. Development agencies would commit to and be held financially accountable for outcomes, that is, real improvements in welfare indicators. The paper describes the role of the evaluation function in aligning incentives with the ultimate goal of improving lives and provides examples of emerging solutions.